SEROPREVALENCE OF EQUINE HERPES VIRUS TYPE-1 IN HORSES AND DONKEYS IN QALUBIAH GOVERNORATE IN EGYPT - Hazem M. El Moghazy; Mohamed G. Abdelwahab; Faiysal I. Hamouda; Elsayed M. Ibrahim; Safaa M.A. Warda (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2017)
Equine hepesirus-1 (EHV-1) is among the infectious diseases that threaten equine health. EHV-1 infects horses causing epidemic respiratory disease, abortion in pregnant mares, neonatal foal death, myeloencephalopathy, and chorioretinpathy. The present study was designed to investigate the presence of EHV-1 in blood serum of horses and donkeys in different localities in Qalubiah Governorate. A total of 185 blood serum samples were collected from horses and donkeys. All animals were evaluated based off whether they were of Indigenous breeds, different ages, apparent health, and clinical signs to equine herpes. The collected blood serum samples were investigated against equine herpes virus type-1 by using an indirect ELISA. The results revealed that 39.5% (73/185) of all horses and donkeys’ sera samples were EHV-1 seropositive while 42.86 % (33/77) of the horses’ sera samples and 37 % (40/108) of the collected donkeys’ sera samples were EHV-1 seropositive. Meanwhile, 57.14 % (44/77) in horses and 63 % (68/108) in donkeys’ sera samples were found to be seronegative for the EHV-1 infections. Analysis of data revealed that, young animals (<2 years) were represent (50%) (14/28) while adult animals (≥2years) were (37.6%) (59/157) EHV-1 antibodies seropositive. Further analysis showed that, EHV-1 antibodies seropositive young horses (9/17) (52.9%) were higher than their adults (40%) (24/60). While, EHV-1 antibodies seropositive young donkeys (45.5%) (5/11) were higher than their adults (36.1%) (35/97). In the present study, the total number of (185) examined horses and donkeys’ sera were differentiated into (79) males and (106) females. Out of (79) male cases, 15.2% (12/79) of total male horses and donkeys were EHV-1 seropositive while 15.15% (5/33) of male horses’ sera and 15.2% (7/46) of male donkeys’ sera were EHV-1 seropositive. However, out of (106) female cases, 57.5% (61/106) of total female horses and donkeys were EHV-1 seropositive. While, the percentage of seropositive sera samples of female horses and donkeys were 63.6% (28/44) and 53.2% (33/62) respectively.